The Role of Leaders in Stimulating Innovative Work Behavior and its Impacts towards Job Performance (Case Study: PT. XYZ) - Harlianto, Jefta; ., Rudi; Afandy, Dessy (International Journal of Engineering and Technology, 2018)
Nowadays, companies are operating in a changing world and competitive market. PT. XYZ realizes that innovation is the key for company to be able to remain competitive. Creating an innovative environment within the company requires both leaders’ role and employees’ involvement. Leaders should have a role to empower employees to be innovative in the workplace. Employees with innovative work behavior will drive their individual job performance, thus improving organization performance. The aim of this study is to examine the role of PT. XYZ’s leaders in stimulating innovative work behavior of their employees. This study applied seven leader behaviors of J. P. J. De Jong & Hartog (2007) that have direct impact in stimulating innovative work behavior of employee. A paper based questionnaire was used to collect the data about employee perception about their leaders’ roles, innovative work behavior and job performance. Based on Slovin formula sampling technique, there were 299 respondents from 815 employees’ population taken for this study. Partial Least Square Method is used to find the significant level between multiple dependent variables and multiple independent variables. The result of this study found that Consulting (T-statistics=2.815, p-value=0.003), Providing Resources (T-statistics=2.510, p-value= 0.006) and Task Assignment (T-statistics=3.250, p-value=0.001) have significant effect on employee innovative work behavior. Although Delegating, Supporting for innovation, Recognizing, and Monitoring from the leaders have no significant effect on innovative work behavior, the organization might provide effect to these four behaviors. The result also shows that employee innovative work behaviors have significant effect on Job Performance (T-statistics=2.503, p-value=0.006).